Ectopic Expression of a Self-Incompatibility Module Triggers Growth Arrest and Cell Death in Vegetative Cells . Issue 4 (19th June 2020) - Lin, Zongcheng; Xie, Fei; Triviño, Marina; Karimi, Mansour; Bosch, Maurice; Franklin-Tong, Vernonica E.; Nowack, Moritz K.
Abstract : Papaver rhoeasS-determinants, which specify self-incompatibility and rejection of self-pollen, trigger growth arrest and programmed cell death in vegetative Arabidopsis tissues when expressed ectopically. Abstract: Self-incompatibility (SI) is used by many angiosperms to reject self-pollen and avoid inbreeding. In field poppy ( Papaver rhoeas ), SI recognition and rejection of self-pollen is facilitated by a female S -determinant, PrsS, and a male S -determinant, PrpS . PrsS belongs to the cysteine-rich peptide family, whose members activate diverse signaling networks involved in plant growth, defense, and reproduction. PrsS and PrpS are tightly regulated and expressed solely in pistil and pollen cells, respectively. Interaction of cognate PrsS and PrpS triggers pollen tube growth inhibition and programmed cell death (PCD) of self-pollen. We previously demonstrated functional intergeneric transfer of PrpS and PrsS to Arabidopsis ( Arabidopsis thaliana ) pollen and pistil. Here, we show that PrpS and PrsS, when expressed ectopically, act as a bipartite module to trigger a self-recognition:self-destruct response in Arabidopsis independently of its reproductive context in vegetative cells. The addition of recombinant PrsS to seedling roots expressing the cognate PrpS resulted in hallmark features of the P . rhoeas SI response, including S -specific growth inhibition and PCD of root cells. Moreover, inducible expression of PrsS in PrpS -expressing seedlings resulted in rapid death of the entire seedling. This demonstrates that, besides specifying SI, the bipartite PrpS-PrsS module can trigger growth arrest and cell death in vegetative cells. Heterologous, ectopic expression of a plant bipartite signaling module in plants has not been shown previously and, by extrapolation, our findings suggest that cysteine-rich peptides diversified for a variety of specialized functions, including the regulation of growth and PCD.